The Defeat of the Arabs in Nizar Qabbani's "Hawamish 'ala Daftar an-Naksah" Poem (Roland Barthes Semiotics Study) - Andini, Happy Nur; Al-Hamim, Muhammad Faishol (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2024)
This study aims to describe the Arab defeat implied in the poem "HawÄmish 'ala Daftar an-Naksah" by Nizar Qabbani through the process of translation and in-depth analysis. This research uses a qualitative-descriptive method by observing existing data, looking for patterns of relationships with various concepts, analyzing, then providing understanding and explanation. The data were collected through literature study and internet search, then analyzed using Roland Barthes' semiotic theory. The results of this study show that from the analysis of 12 stanzas of poetry, denotation and connotation meanings were found that reflect the defeat of the Arabs. Through this analysis, it is hoped that readers can understand the poem "Hawamish 'ala Daftar an-Naksah" both from its literal meaning and implicit meaning.